#### Answer

x = 2
y = 0
(2, 0)

#### Work Step by Step

$2x + y = 4$
$x - y = 2$
Add the second equation to the first one
$2x+y+x-y=4+2$
$3x = 6$
$x = 2$
Substitue for x to solve for y
$2 - y = 2$
$y = 0$

Published by
Cengage Learning

ISBN 10:
1-13311-087-8

ISBN 13:
978-1-13311-087-3

x = 2
y = 0
(2, 0)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.